Contribution of Microglia-Mediated Neuroinflammation to Retinal Degenerative Diseases - Maria H. Madeira; Raquel Boia; Paulo F. Santos; António F. Ambrósio; Ana R. Santiago (Hindawi Limited, 2015)
Retinal degenerative diseases are major causes of vision loss and blindness worldwide and are characterized by chronic and progressive neuronal loss. One common feature of retinal degenerative diseases and brain neurodegenerative diseases is chronic neuroinflammation. There is growing evidence that retinal microglia, as in the brain, become activated in the course of retinal degenerative diseases, having a pivotal role in the initiation and propagation of the neurodegenerative process. A better understanding of the events elicited and mediated by retinal microglia will contribute to the clarification of disease etiology and might open new avenues for potential therapeutic interventions. This review aims at giving an overview of the roles of microglia-mediated neuroinflammation in major retinal degenerative diseases like glaucoma, age-related macular degeneration, and diabetic retinopathy.